Translation, cross-cultural adaptation and validation of English start back screening tool into Bangla for patients with low back pain - Hasan, Md. Israt; Ahmed, Syed Mozaffar (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This study was intended to translate and culturally adapt the STarT back screening tool to produce an equivalent Bangla version. Total 58 patients with low back pain completed the newly developed Bangla version of STarT back screening tool and Bangla version of Ronald Morris Disability Questionnaire seven days apart. Reliability was assessed by internal consistency (Chronbach’s alpha for overall score 0.81 and for spychosocial subscale was 0.76) and test-retest reliability (intraclass correlation coefficient for overall score was 0.78 and for spychosocial subscale was 0.71). Reliability of Bangla version of STarT back screening tool was very good. Pearson’s correlation coefficient was carried out on the Bangla version of STarT back screening tool and Bangla version of RMDQ to assess construct validity (overall score was 0.88 and spychosocial subscale score was 0.83) which indicate a strong correlation between them. This study shows that the Bangla version of STarT back screening tool is a reliable, valid and culturally adapted responsive screening tool for the patients with low back pain.